2009
DOI: 10.3354/meps08177
|View full text |Cite
|
Sign up to set email alerts
|

Variability in transport of fish eggs and larvae. III. Effects of hydrodynamics and larval behaviour on recruitment in plaice

Abstract: Transport of plaice eggs and larvae in the southern North Sea was modelled using a finite-volume advection-dispersion model with high spatial and temporal resolution. Hydrodynamic forcing was based on actual river discharge and meteorological data for a 7 mo period in the winter and spring of 1989 and 1996 to 2003. Egg and larval development was linked to temperature and each developmental stage had its own physical and behavioural properties. Two hypotheses on transport mechanisms in the late larval stages we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 39 publications
(57 reference statements)
5
109
0
2
Order By: Relevance
“…The relationship between larval development time and temperature was calculated from published values (see Bolle et al 2009). The relationship takes the form of ln(D) = 5.0 -0.15T, where D is larval stage duration in days and T is temperature in °C.…”
Section: Larval Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between larval development time and temperature was calculated from published values (see Bolle et al 2009). The relationship takes the form of ln(D) = 5.0 -0.15T, where D is larval stage duration in days and T is temperature in °C.…”
Section: Larval Datamentioning
confidence: 99%
“…van der Veer & Witte 1999). Next, the observed relationship between larval development times and prevailing water temperatures was compared to experimental (Talbot 1977) and other growth data (compiled in Bolle et al 2009) and deviations were considered to indicate the occurrence of poor growth or starvation conditions. Finally, the relationship between abundance of immigrating larvae and temperature during the pelagic period (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several recent genetic studies have shown substantial spatial heterogeneity between life stages and temporal variability in genetic structure with metapopulations (Hogan et al, 2010;Selkoe et al, 2010). Likewise, several studies have explored hypotheses of oceanographic variability to explain fine-scale genetic patchiness (Banks et al, 2007) or chaotic genetic patchiness (Hogan et al, 2010), and certain larval transport models suggest that large variations in PLD and recruitment patterns could even be linked to hydrodynamic variability (Bolle et al, 2009;Connolly & Baird, 2010). Indeed, even knowledge of the PLD is not sufficient to predict scales of dispersal and gene flow among populations (Mitarai et al, 2009;Weersing & Toonen, 2009).…”
Section: Connectivity In Marine Ecologymentioning
confidence: 99%
“…Under stratified conditions, a subsurface jet induced by density differences transports water around the north, east, and south-east slopes of the Dogger Bank into the Oyster Grounds (Brown et al, 1999;Hill et al, 2008). The thermal stratification breaks down in the autumn, and is absent throughout the winter.…”
Section: Southern North Seamentioning
confidence: 99%